Integrative systematic revision of a new genus of Eumolpinae (Coleoptera: Chrysomelidae) endemic to New Caledonia: Dematotrichus gen. nov. and its numerous new hairy species. Issue 1 (31st December 2022) - Gómez-Zurita, JesúS
Abstract : The monophyletic group of species around Dematochroma pilosa Jolivet, Verma & Mille is identified in this work by combining information from mitochondrial DNA data and morphological features. A series of defining traits diagnosing this species assemblage from its closest phylogenetic relatives, including the genera Thasycles Chapuis and Atrichatus Sharp, is used to argue for its taxonomic separation and propose a new genus, named Dematotrichus gen. nov. Both Dematochroma pilosa and Montrouzierella hispida Jolivet, Verma & Mille are transferred to the new genus as D. pilosus (Jolivet, Verma & Mille) comb. nov. and D. hispidus (Jolivet, Verma & Mille) comb. nov., and 11 new species are described: D. capillaris sp. nov., D. capillosus sp. nov., D. comans sp. nov., D. crinitus sp. nov., D. comatulus sp. nov., D. hirtus sp. nov., D. hirsutus sp. nov., D. horridus sp. nov., D. pubescens sp. nov., D. setosus sp. nov. and D. villosus sp. nov. The work includes an identification key for all the species in the new genus. http://zoobank.org/urn:lsid:zoobank.org:urn:lsid:zoobank.org:pub:0A3640A2-28B4-4592-9883-0DDB82BE4DB2